Exploring long COVID in pediatric patients: clinical insights from a long COVID clinic - Kamel, Dina; Vu, My H.; Bender, Jeffery; Warburton, David; Wood, John C.; Mohandas, Sindhu (Frontiers in Pediatrics, 2025)
BackgroundLong COVID describes the persistence or recurrence of symptoms beyond the acute phase of SARS-CoV-2 infection and is increasingly recognized in children and adolescents. Despite its prevalence, understanding of symptom patterns and the influence of vaccination on disease trajectory in pediatric populations remains limited.MethodsWe conducted a retrospective study of patients aged 0–21 years evaluated at the Long COVID Clinic at Children's Hospital Los Angeles between August 2021 and November 2023. Patients were included if they reported persistent or new symptoms ≥4 weeks after SARS-CoV-2 infection.ResultsA total of 123 patients were enrolled. The mean age was 13.1 years, and 51% were male. Symptom onset occurred a mean of 5 weeks after infection. At presentation, 56% of patients reported symptoms lasting 0–24 weeks, 28% for 25–52 weeks, and 16% for >52 weeks. Fatigue (93%) and headache (70%) were the most prevalent symptoms in both younger (<12 years) and older (>12 years) cohorts. Female patients more frequently reported brain fog, dizziness, palpitations, and postural orthostatic tachycardia syndrome. Overall symptom burden decreased significantly over time (p < 0.001). Vaccination status at baseline was not associated with difference in symptom duration on initial presentation (p = 0.4). However, among those vaccinated after developing long COVID, 41% reported subjective improvement in the following weeks.ConclusionPediatric long COVID is marked by prolonged, multisystem symptoms. Vaccination may offer symptomatic benefit for some patients, though larger prospective studies are necessary to better define its role.